2007
DOI: 10.1577/1548-8446(2007)32[372:arotcs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Conservation Status of Crayfishes of the United States and Canada after 10+ Years of Increased Awareness

Abstract: The American Fisheries Society Endangered Species Committee herein provides a list of all crayfishes (families Astacidae and Cambaridae) in the United States and Canada that includes common names; state and provincial distributions; a comprehensive review of the conservation status of all taxa; and references on biology, conservation, and distribution. The list includes 363 native crayfishes, of which 2 (⟨ 1%) taxa are listed as Endangered, Possibly Extinct, 66 (18.2%) are Endangered, 52 (14.3%) are Threatened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
230
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(236 citation statements)
references
References 31 publications
4
230
0
2
Order By: Relevance
“…The reproductive mode of marbled crayfish, later identified as apomictic parthenogenesis (Martin et al, 2007), allows a single female to establish a viable population not only in aquarium conditions but in principle also in the wild. These exclusively female aquarium stocks, for several years of unclear taxonomic position, were confirmed to belong to the slough crayfish Procambarus fallax (Martin et al, 2010), an American species occurring in Florida and Georgia (Taylor et al, 2007). In its native range, however, all-female populations have never been found.…”
Section: > Procambarus Fallax F Virginalis; Marbled Crayfish (Figurementioning
confidence: 90%
See 1 more Smart Citation
“…The reproductive mode of marbled crayfish, later identified as apomictic parthenogenesis (Martin et al, 2007), allows a single female to establish a viable population not only in aquarium conditions but in principle also in the wild. These exclusively female aquarium stocks, for several years of unclear taxonomic position, were confirmed to belong to the slough crayfish Procambarus fallax (Martin et al, 2010), an American species occurring in Florida and Georgia (Taylor et al, 2007). In its native range, however, all-female populations have never been found.…”
Section: > Procambarus Fallax F Virginalis; Marbled Crayfish (Figurementioning
confidence: 90%
“…Thanks to broad native range and extensive introductions, the virile (or Northern) crayfish was considered the most widespread crayfish species in the United States and Canada, inhabiting over 40 states (Taylor et al, 2007). However, recent phylogeographic and phylogenetic studies revealed that it is actually a diverse species complex (Mathews and Warren, 2008;.…”
Section: > Orconectes Cf Virilis; Virile Crayfish (Figure 9)mentioning
confidence: 99%
“…Many sellers used scientific species names in their auction listings, and the species identification was that given by the seller, which may or may not be accurate (Keller and Lodge, 2009). When sellers described crayfish using a common name, I searched for whether that name appeared in Taylor et al (2007), and used the scientific name from that list. For some auctions, the descriptions in the listing did not allow a tentative species identification, and were counted as unknown.…”
Section: Methodsmentioning
confidence: 99%
“…While much of the research on the sale of crayfish as pets has focused on the possibility of the introduction of exotic species (Chucholl, 2013;Papavlasopoulou et al, 2014;Soes and Koese, 2010), how those species are initially sourced can also be a concern (Calado et al, 2003;Lukhaup, 2015). North America is home to more crayfish species than anywhere else in the world (Crandall and Buhay, 2008;Richman et al, 2015), but about half of North American species pose some sort of conservation concern (Taylor et al, 2007). It is possible that within North America, collectors could harm native North American crayfish species by exploiting local populations for selling at auction.…”
Section: Introductionmentioning
confidence: 99%
“…3). (Taylor et al 2007), and assigned G2 ranking using Master (1991) global conservation criteria for conservation listing due to (1.) its limited range and (2.)…”
Section: Systematicsmentioning
confidence: 99%